2013
DOI: 10.1002/kin.20766
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the CCl2 Radical Recombination Reaction by Laser‐Induced Fluorescence Technique

Abstract: An experimental setup that coupled IR multiple‐photon dissociation (IRMPD) and laser‐induced fluorescence (LIF) techniques was implemented to study the kinetics of the recombination reaction of dichlorocarbene radicals, CCl2, in an Ar bath. The CCl2 radicals were generated by IRMPD of CDCl3. The time dependence of the CCl2 radicals’ concentration in the presence of Ar was determined by LIF. The experimental conditions achieved allowed us to associate the decrease in the concentration of radicals to the self‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(80 reference statements)
1
2
0
6
Order By: Relevance
“…For all HCl pressures, the self‐recombination reaction takes place in the high‐pressure limit regime. The value of the self‐recombination rate constant was obtained from the mean value of the rate constants obtained for HCl pressures between 5 and 40 Torr and resulted in truerightkT=(5.7±0.1)×1013 cm 30.16em molecule 10.16emnormals1in excellent agreement with that obtained in a previous work . The rate constant obtained for the reaction between CCl 2 radicals in their ground state and HCl was truerightk HCl =(2.7±0.1)×10140.16em cm 30.16em molecule 10.16emnormals1…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…For all HCl pressures, the self‐recombination reaction takes place in the high‐pressure limit regime. The value of the self‐recombination rate constant was obtained from the mean value of the rate constants obtained for HCl pressures between 5 and 40 Torr and resulted in truerightkT=(5.7±0.1)×1013 cm 30.16em molecule 10.16emnormals1in excellent agreement with that obtained in a previous work . The rate constant obtained for the reaction between CCl 2 radicals in their ground state and HCl was truerightk HCl =(2.7±0.1)×10140.16em cm 30.16em molecule 10.16emnormals1…”
Section: Resultssupporting
confidence: 85%
“…[CCl 2 ] 0 represents the initial concentration of radicals. In , we have demonstrated that with the TEA CO 2 laser fluence at the focus of this work, every CDCl 3 molecule within the observation volume is dissociated; so that in all the experiments, the initial concentration of CCl 2 radicals is 1 Torr. Considering that the LIF signal is proportional to the radicals' concentration, the detected signal (S D ) will be given by truerightSD=qi0.16em[ CCl 2](t)0.16em+0.16emS0where S 0 is the background signal in the absence of CCl 2 radicals, q i is a constant that accounts for experimental factors such as the photomultiplier responsivity, the proportion of the fluorescence signal emitted in the observation solid angle, the ratio of the number of radicals in the observation volume to the total number of radicals excited by the dye laser and the lenses, filter, and iris transmission.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…En nuestros estudios de la cinética de reacción del radical CCl 2 con CCl 2 [9] , con HCl [10] y con O 2 [11] , el mismo se obtuvo a partir de la Disociación Multifotónica Infrarroja de CDCl 3 [12] . El cloroformo es empleado en numerosos procesos industriales como la fabricación de colorantes, pesticidas y propelentes.…”
Section: Introductionunclassified
“…En los estudios de la descomposición térmica de CHCl 3 , Won et al [14] y Zhu et al [15] presentan valores para las constantes de velocidad de la reacción de recombinación entre radicales CCl 2 para formar C 2 Cl 4 y C 2 Cl 3 +Cl. En nuestro laboratorio hemos determinado la constante de velocidad de la reacción CCl 2 + CCl 2 → C 2 Cl 4 a 298 K y presiones entre 1 y 30 Torr [9] . En un trabajo posterior determinamos la dependencia de dicha constante con la temperatura y con la presión empleando los formalismos SSACM y SACM/CT de la teoría de reacciones unimoleculares [16] .…”
Section: Introductionunclassified